1998
DOI: 10.1002/(sici)1097-0290(19980105)57:1<46::aid-bit6>3.3.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing seeding and culture methods to engineer smooth muscle tissue on biodegradable polymer matrices

Abstract: The engineering of functional smooth muscle (SM) tissue is critical if one hopes to successfully replace the large number of tissues containing an SM component with engineered equivalents. This study reports on the effects of SM cell (SMC) seeding and culture conditions on the cellularity and composition of SM tissues engineered using biodegradable matrices (5 x 5 mm, 2-mm thick) of polyglycolic acid (PGA) fibers. Cells were seeded by injecting a cell suspension into polymer matrices in tissue culture dishes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
65
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(67 citation statements)
references
References 0 publications
2
65
0
Order By: Relevance
“…As compared to the methods described in the literature, 4,[6][7][8][9][10][11][12] where the seeding process usually takes hours to days, the present SAW method significantly accelerates the cell seeding process. The fast seeding time also means that multiple drops containing the cells can be successively driven into the scaffold to achieve greater cell loading.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…As compared to the methods described in the literature, 4,[6][7][8][9][10][11][12] where the seeding process usually takes hours to days, the present SAW method significantly accelerates the cell seeding process. The fast seeding time also means that multiple drops containing the cells can be successively driven into the scaffold to achieve greater cell loading.…”
Section: Discussionmentioning
confidence: 95%
“…As we mentioned before, there are various cell seeding methods being developed and most of these studies investigate the cell viability and functionality. 4,[6][7][8][9][10][11][12] Undoubtedly, cell viability and functionality are critical to the usefulness of any new technique for tissue engineering. 5 Therefore, in addition to high cell viability, the proliferation and differentiation ability of the treated cells showed no difference from those of the untreated cells, indicating that the SAW has no deleterious effects on the cells' functionality.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been a challenge, however, to seed cells evenly in a three-dimensional, porous scaffold 4 . For example, the most commonly used cell seeding technique, gravity cell seeding, usually results in a vertical cell density gradient within the scaffold 5 . Alternative methods, such as the use of spinning flasks 6 or vacuum chamber 7 , showed improved cell seeding, and more uniform cell and matrix distribution in the construct.…”
Section: Introductionmentioning
confidence: 99%
“…The seeding method, static or dynamic, influences the seeding efficiency and homogeneity. Some studies claim more efficient seeding [198], whereas others found lower seeding efficiency in a spinner flask compared to static seeding [199,200]. More homogeneous [200] or less uniform cell distribution [199] was also observed.…”
Section: Ebcell Ebsmentioning
confidence: 99%